PENGARUH INVESTMENT OPPORTUNITY SET, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN RETURN ON ASSET TERHADAP NILAI PERUSAHAAN - Gita Syardiana; Ahmad Rodoni; Zuwesty Eka Putri (Akuntabilitas, 2015)
The purposes of this research to analyze the effects of investment opportunityset (IOS), structure capital, growth, and return on asset (ROA) to firm’s value. This researchused all the companies listed on Indonesian Exchange in the peroid 2012 until 2014. Thenumber of all companies that were became in this study were 119 companies with 3 yearobservation. Based on method purposive sampling, research sample total is 357 financialstatements and annual report. Data analyzed by regression data panel. Result of this researchindicates that investment opportunity set (IOS), growth, and return on asset (ROA)influences significantly positive on the firm value, while structure capital does not influencesto firm valueDOI: 10.15408/akt.v8i1.2760